Consumer Green Behavior and Sustainability Accounting-Based Marketing Innovation: A Systematic Framework for Eco-Brand Engagement - Muhammad Zabir Zainuddin; Sulvariany Tamburaka; Nasrullah Dali (Ilomata International Journal of Tax and Accounting, 2025)
This study develops a systematic framework that integrates consumer green behavior, sustainability-oriented marketing innovation, and sustainability accounting mechanisms in relation to eco-brand engagement. A qualitative systematic review was conducted using PRISMA 2020 procedures and thematic synthesis. In total, 38 peer-reviewed journal articles addressing green consumer behavior, sustainability marketing practices, sustainability disclosure, and eco-brand engagement were identified, screened, and analyzed. The literature suggests that eco-brand engagement is associated with the dynamic interaction among consumer environmental orientation (values, beliefs, attitudes, norms, perceived control, and social influence), sustainability-oriented marketing innovation (green products, processes, communication, and business models), and a sustainability accounting-based governance layer that may strengthen measurement, control, and disclosure credibility. Across the reviewed empirical and conceptual studies, engagement appears to be stronger when marketing innovation is supported by verifiable sustainability performance information, including environmental management accounting, sustainability performance indicators, and credible ESG reporting and assurance, which may help mitigate greenwashing risk and information asymmetry. The reviewed literature also indicates that stakeholder and institutional pressures are likely to influence both innovation priorities and disclosure practices, while engagement outcomes such as trust, loyalty, advocacy, and co-creation may provide feedback signals that inform subsequent strategic and resource allocation decisions. Overall, this framework points to eco-brand engagement not only as a behavioral and marketing-related outcome, but also as a governance- and accountability-related outcome linked to sustainability accounting.